HASIL BELAJAR MODEL PROBLEM BASED LEARNING DAN KOOPERATIF TIPE GROUP INVESTIGATION - Rogandi Damayanto; Agus Suyatna; Undang Rosidin (Jurnal Pembelajaran Fisika, 2012)
The aims of study is to enhance learning achievement. The experimental design of this research is Pre-Experimental Design type of One-Group Pretest-Posttest Design. This research was conducted in SMK 2 Mei Bandar Lampung that exerting 2 experimental class. The studying’s result measured by pretest and posttest evaluation score that use N-gain score and the hypothesis testing that use Independent Sample t Test. The objectives of this research are to find out : (1) the differences of the average of student’s studying result of cognitive aspect in physics learning that the learning process used PBL which the learning process used Cooperative Learning type of GI, (2) to find out the highest of physivs’s studying result between PBL model and cooperative learning model type of GI based on the capability of student’s cognitive. The result indicated that there was an average differences of studying’s result in every experimental class and on the average of N-gain score. The increasement of Problem Based Learning average score is higher than Group Investigation, therefore Problem Based Learning is more effective applicated as an effort to increase the student’s studying result in learning.Keyword : Problem Based Learning, Cooperative Type of GI, Studying’s Result.